Secret Agent Elephant - McLaughlin Eoin (London; Orchard Books, 2019)
Watch out, supervillains. There's a new spy in town. Secret Agent Elephant isn't much good at hiding, or disguises, or driving fast cars but he DOES look dangerously handsome in a tuxedo. Join the world's biggest, clumsiest super spy on his first mission: to find feline supervillain Vincent le Morte and stop him from destroying the world. Good luck, Agent Elephant. The world is counting on you. AND REMEMBER: DO NOT GET DISTRACTED BY THE MINI PIZZAS!
Keywords: Children's stories